Outcomes of Trabeculectomy Augmented With Subconjunctival and Subscleral Ologen Implantation in Primary Advanced Glaucoma. Issue 1 (January 2017) - Angmo, Dewang; Wadhwani, Meenakshi; Upadhyay, Ashish Dutt; Temkar, Shreyas; Dada, Tanuj
Abstract : Purpose: To evaluate the efficacy and safety of trabeculectomy with combined subconjunctival and subscleral ologen implant in eyes with advanced glaucomatous optic neuropathy. Design: This is a retrospective, noncomparative case series. Methods: Twenty seven eyes of 23 patients with advanced primary glaucoma who underwent fornix-based trabeculectomy with insertion of ologen both subsclerally and subconjunctivally along with low dose Mitomycin-C (0.1 mg/mL×1 min) were evaluated. Data recorded included a complete history, demographic profile, and ophthalmic examination including gonioscopy and visual fields. Any complications or secondary procedures performed after trabeculectomy were recorded. Complete success was defined as intraocular pressure (IOP) ⩽15 mm Hg without ocular hypotensive medication and qualified success as IOP⩽15 mm Hg with medications. Results: The average age of patients was 46.2±14.8 years. There were 17 males and 6 females. Of these, 7 patients were diagnosed with juvenile open-angle glaucoma, 7 patients with primary open-angle glaucoma and 9 patients with primary angle-closure glaucoma and pseudophakia. The average follow-up time was 23.3±5.6 months, with a minimum of at least 12 months. The mean preoperative IOP was 38.3±6.6 mm Hg. Postoperatively, the IOP at 3 months was 12.5±1.9 mm Hg; 6 months was 12.6±3.9 mm Hg; 12 months was 12.3±2.5 mm Hg; and 24 months was 12.5±1.6 mm Hg (n=17); ( P <0.0001). Complete success was noted in 92.6% eyes, qualified success in 3.7% eyes, and failure in 3.7% eyes. The preoperative and postoperative best-corrected visual acuity in logarithm of the minimum angle of resolution was 0.3±0.2 and 0.3±0.1 ( P =0.31). The average number of ocular hypotensive medications used preoperatively was 4.2±0.5 (median 4) which decreased to 0.07±0.3 (median 0), ( P <0.0001) postoperatively. Conclusions: Trabeculectomy with low dose Mitomycin-C and with implantation of ologen both subsclerally and subconjunctivally, appears to offer encouraging results in achieving a low target IOP in eyes with advanced primary adult glaucoma.